Detection of vascular bundles using cell wall birefringence on exposure to polarized light - Yoshinori Murata; Satoshi Kubo; Eiji Togawa; Siti Fatimah Mhd Ramlee; Othman Sulaiman; Rokiah Hashim; Wan Asma Ibrahim; Akihi Kosugi; Akiko Hirooka; Hisashi Abe (2015)
Vascular bundles (VBs) of oil palm trunks exhibited birefringence due to polarized orientation of their cell wall components, although another component of the trunks, parenchyma tissue (PT), did not. The intensity of the birefringence depended on the VB composition; therefore, it was possible to estimate the VB content readily using a polarizing microscope connected to an image analyzer. The method proposed in this manuscript should allow easier quantification of VBs in oil palm trunks than methods using X-ray diffraction. Both VBs and PT contained cellulose, hemicelluloses, lignin, and starch; however, the cellulose content of PT was less than half that of VBs. This difference in cellulose content between VB and PT may explain why VBs were detected under polarizing light